The frugal economy : a guide to building a better world with less - Radjou, Navi (John Wiley & Sons, Inc., 2025)
"As climate change worsens, businesses bear a moral responsibility to respect the planetary boundaries and reduce the "negative externalities" of their economic activities. This is why all businesses are now being asked to Do LESS (harm). But here is the big problem: we humans are not born to do LESS. We are wired to do MORE. Nothing in Nature is designed to do less. All creatures on Earth are animated by an evolutionary need to do -- and be(come) -- more. Certain limits -- like planetary boundaries -- are worth respecting and you need to "play within (those) limits" and DO LESS. But other limits -- physical, mental, scientific -- need to be crossed to push out the boundaries of what humans can achieve, so we can DO MORE. Especially, we need to break our self-limiting belief that "we are all small" and strive to BE MORE. From a Christian perspective -- as well as a Hindu and Buddhist viewpoint -- leading a frugal life consists in doing less harm (to people and Nature) as well as doing more good (to others). A frugal life is about living better with less. A frugal economy will raise our consciousness so we can all stretch our mental and psychic limits and become better human beings while harming less our environment and respecting the planetary limits. A frugal economy will enable humanity to wisely "continue to develop and thrive for generations to come" while "playing" within the boundaries of our collective home: Earth"-- Provided by publisher.
Keywords: Sustainable development.; Sustainable living.; elektronické knihy; electronic books